The Effectiveness of the Flipped Classroom Learning Model to Improve Mathematics Learning Outcomes at MTS Amalul Ikhlas - Ihda, Robiatul; Harahap, Tua Halomoan (Lembaga Riset Mutiara Akbar, 2022)
The formulation of the problem in this research is to find out the results of learning mathematics using the expository model and the flipped classroom learning model and whether the flipped classroom learning model is effective in improving the mathematics learning outcomes of MTs Amalul Ikhlas students. This research is a quantitative study. The population in this study were students of class VII MTs Amalul Ikhlas which consisted of 2 classes totaling 54 students. Sampling was done by using saturated sampling technique. The sample in this study consisted of two classes, namely VII A totaling 27 students as the experimental class and VII B totaling 27 students as the control class. control class is 46,48148. From the post-test results, the average score in the experimental class was 80.741 while the post-test average in the control class was 66.6667. From the data analysis shows that the experimental class, the value of L0 pre-test = 0.096 and the value of L0 post-test = 0.130. Meanwhile for the control class the value of L0 pre-test = 0.111 and the value of L0 post-test = 0.119. To test the homogeneity of the pre-test experimental class and control class obtained Fhitung (1.047) < F table (1.929). For the homogeneity test in the post-test experimental class and control class obtained Fhitung (1,108) <Ftable (1,929). The results of descriptive analysis of the data and gain index of the experimental class and control class show that the average gain index of the experimental class is 0.7 and the control class is 0.4. Furthermore, from the results of the t-test calculation, obtained thitung (5,281) > ttable (2,006) meaning that the average student learning outcomes on integer material with the Flipped Classroom learning model are higher than student learning outcomes using the Expository learning model and the Flipped Classroom learning model. effective in improving students' mathematics learning outcomes.